Women’s Clothing Application by Using Waterfall Method in the Form of Website of Rafika Modes UMKM - Syahrul Ibnu Rafi; Uce Indahyanti (Procedia of Engineering and Life Science, 2022)
This research is the existence of problems in the scope of the sales information system. The problem is in the form of inefficient and widespread in marketing the products of this women's clothing UMKM. This is because the owner of UMKM does not understand the current technology. So that the sales results are less able to compete with other UMKM in the society. The existence of this women's clothing sales application makes it easier to market products and expand customer reach. In this paper, the writer uses the waterfall development model which an approach to software development that determines the stages of making a website from software requirements analysis, design, program code making, testing and support or maintenance. The web-based women's clothing sales application can make it easier for UMKM owner Rafika Modes to sell products that have been produced and provide reports for what products are sold. The application is in the form of web, so the user is more flexible to open the application with any devices.